Use the Product Rule of Exponents to simplify 510⋅55(1 point)
Responses
515
5 superscript 15 baseline
2550
25 superscript 50 baseline
550
5 superscript 50 baseline
2515
9 answers
2 superscript 50 baseline
5^10x5^5
To simplify this expression using the Product Rule of Exponents, we need to add the exponents together because the bases (5) are the same.
5^10 × 5^5 = 5^(10+5) = 5^15.
So, the simplified expression is 5^15.
5^10 × 5^5 = 5^(10+5) = 5^15.
So, the simplified expression is 5^15.
9^9x9^-6
To simplify this expression using the Product Rule of Exponents, we need to subtract the exponents because the bases (9) are the same.
9^9 × 9^(-6) = 9^(9-6)= 9^3.
So, the simplified expression is 9^3.
9^9 × 9^(-6) = 9^(9-6)= 9^3.
So, the simplified expression is 9^3.
Simplify 12^87divided12^25
To simplify this expression, we use the Quotient Rule of Exponents, which states that when dividing two powers with the same base, we subtract the exponents.
12^87 ÷ 12^25 = 12^(87-25) = 12^62.
So, the simplified expression is 12^62.
12^87 ÷ 12^25 = 12^(87-25) = 12^62.
So, the simplified expression is 12^62.
7^8divided7^5
To simplify this expression, we use the Quotient Rule of Exponents, which states that when dividing two powers with the same base, we subtract the exponents.
7^8 ÷ 7^5 = 7^(8-5) = 7^3.
So, the simplified expression is 7^3.
7^8 ÷ 7^5 = 7^(8-5) = 7^3.
So, the simplified expression is 7^3.